Fecal calprotectin and its association with functional dyspepsia in children - Jeanette Manoppo; Rizal Somali; PITIKA ASPR (Paediatrica Indonesiana, 2020)
Background Calprotectin is a calcium-binding protein found normally in small amounts within the digestive tract. Fecal calprotectin measurement is used as a biomarker to identify digestive tract inflammation. Functional dyspepsia is one of the most common health issues in children, occurring in 3-27%, and accounts for considerable quality of life impairment and health care expenses. Objective To determine fecal calprotectin concentration in generally healthy children as well as to assess for a possible association between fecal calprotectin and functional dyspepsia. Methods This cross-sectional study was conducted from February to April 2019 in primary school-aged children in Manado, North Sulawesi. Subjects consisted of 38 children aged 6–12 years. Fecal calprotectin was measured in subjects' stool specimens, and considered to be normal if fecal calprotectin concentration of < 50 ?g/g. Diagnosis of functional dyspepsia was defined using the parent-filled Rome IV questionnaire form. Data were analyzed with Chi-square and Phi-coefficient correlation tests. Results Thirty-eight subjects, 22 boys and 16 girls, were grouped according to fecal calprotectin concentration (normal vs. elevated) and functional dyspepsia diagnosis. Mean fecal calprotectin concentration was 312.45 ?g/g in the functional dyspepsia group and 20.89 ?g/g in the healthy group. Elevated fecal calprotectin was found in 55.6% of the functional dyspepsia group and 10.3% of the healthy group. There was a positive correlation between fecal calprotectin elevation and functional dyspepsia (r=0.471; P=0.004). Conclusion Current fecal calprotectin physiological cut-off level of 50 ?g/g seems valid for children aged 6-12 years. Elevated fecal calprotectin is associated with functional dyspepsia in children.